Cherry tree gum-derived silver/microporous carbon: Reduction of nitroaromatic compounds by microwave-assisted reaction - Hossein Ghafuri; Fariba Gholipour; Peyman Hanifehnejad; Fatemeh Bijari (Heliyon)
In this study, a silver/microporous carbon (Ag@MC) nanocomposite was synthesized using cherry tree gum as a carbon precursor via a hydrothermal method. The catalytic performance of Ag@MC was evaluated for the reduction of nitroaromatic derivatives under solvent-free and microwave-assisted conditions, achieving yields higher than 90 % in just 5 min, significantly shorter than many comparable studies. Comprehensive characterization confirmed the structure and stability of Ag@MC, with silver nanoparticles effectively trapped within its microporous matrix. The nanocomposite demonstrated excellent reusability, maintaining high catalytic activity over six cycles, thereby adhering to green chemistry principles. These findings highlight the potential of using sustainable natural polymers for high-efficiency catalytic applications.